Corrosion Characteristics and Flexural Performance of Carbonated Recycled Aggregate Concrete Beams in Corrosive Environments - Guixiang Yi; Yuanyuan Song; Jian Wang; Bo Chen (Buildings)
The influence of the carbonation of recycled coarse aggregates on the durability performance of the recycled aggregate concrete beams is still unclear. In this study, the corrosion characteristics and flexural performance of the carbonated recycled aggregate concrete (C-RAC) beams in corrosive environments were investigated. The results illustrated that the mass loss of the longitudinal tensile steel bars (LTSBs) in the corroded C-RAC beams decreased when the replacement ratio of the carbonated recycled coarse aggregate (CRCA) increased. Compared to the corroded non-carbonated recycled aggregate concrete (NC-RAC) beam, the mass loss of LTSBs in the corroded C-RAC beam was reduced by 37.91% when the CRCA replacement ratio was 100%. The average mass loss of the short limbs of the stirrups on the tensile side of the corroded C-RAC beam was lower than that of the corroded NC-RAC beam. As the CRCA replacement ratio increased, the flexural performance of the corroded C-RAC beams was enhanced. When the CRCA replacement ratio was 100%, the ultimate load and the displacement ductility coefficient of the corroded C-RAC beam increased by 14.04% and 25.82% compared to the corroded NC-RAC beam, respectively. During the service life, the concrete strains of the cross-section at the mid-span of the corroded C-RAC beams satisfied the assumption of plane section. The research results of this study can provide some reference for the durability design and engineering application of C-RAC beams.